Vector acoustic properties of underwater noise from impact pile driving measured within the water column - Dahl, Peter H.; MacGillivray, Alexander; Racca, Roberto (Frontiers in Marine Science, 2023)
Vector acoustic properties of the underwater noise originating from impact pile driving on steel piles has been studied, including the identification of features of Mach wave radiation associated with the radial expansion of the pile upon hammer impact. The data originate from a 2005 study conducted in Puget Sound in the U.S. state of Washington, and were recorded on a four-channel hydrophone system mounted on a tetrahedral frame. The frame system measured the gradient of acoustic pressure in three dimensions (hydrophone separation 0.5 m) from which estimates of kinematic quantities, such as acoustic velocity and acceleration exposure spectral density, were derived. With frame at a depth of 5 m in waters 10 m deep, the data provide an important look at vector acoustic properties from impact pile driving within the water column. Basic features of the Mach wave are observed in both dynamic (pressure) and kinematic measurements, most notably the delay time T leading to spectral peaks separated in frequency by 1/T∼ 106 Hz, where T equals the travel time of the pile radial deformation over twice the length of the pile. For the two piles studied at range 10 and 16 m, the strike-averaged sound exposure level (SEL) was ∼ 177 dB re 1μPa2-s and the acceleration exposure level (AEL) was 122-123 dB re μm2/s4 s. The study demonstrates an approximate equivalence of observations based on dynamic and kinematic components of the underwater acoustic field from impact pile driving measured within the water column.